Development of science teaching materials based on higher-order thinking skills (HOTS) to enhance higher-order thinking skills in the topic of classification of living things - Fahmi Fahmi; Yudha Irhasyuarna; Ikhwan Khairu Sadiqin; Dini Aprida; Muhammad Fajar; Hery Fajeriadi (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
The need for science teaching materials that effectively foster HOTS remains unmet, as most existing resources focus only on lower-order cognitive levels. Furthermore, no comprehensively validated materials, covering content validity, reliability, and statistical significance, are yet available to ensure the effective integration of HOTS indicators. This study aims to develop Science teaching materials based on Higher-Order Thinking Skills (HOTS) for the topic of classification of living things for Junior High School (JHS) students. The low attainment of students' higher-order thinking skills, characterized by the lack of HOTS material integration in currently available teaching materials, indicates a significant gap between curriculum demands and current instructional practices. The development of these teaching materials is necessary to address this problem and provide a scientific contribution in the form of a tested instrument to improve the quality of Science learning. The research employed the 4D development model (Define, Design, Develop, Disseminate), which was reduced up to the Develop stage. The trial subjects included material experts, instructional design experts, Science teachers, and Grade VII students. Data collection techniques were carried out through expert validation, using quantitative and qualitative descriptive analysis. The validation results show that the teaching materials are highly valid with an average score of 3.72 out of a 4-point scale and a Cronbach’s Alpha reliability value of 0.91, indicating high internal consistency. Abstrak. Kebutuhan bahan ajar IPA yang benar-benar mendukung pengembangan HOTS masih belum terpenuhi karena sebagian besar bahan ajar yang ada hanya menargetkan level kognitif rendah. Selain itu, belum tersedia bahan ajar yang tervalidasi secara komprehensif, meliputi validitas konten, reliabilitas, dan signifikansi statistik, untuk memastikan integrasi indikator HOTS secara efektif. Penelitian ini bertujuan mengembangkan bahan ajar Ilmu Pengetahuan Alam (IPA) berbasis keterampilan berpikir tingkat tinggi (Higher Order Thinking Skills/HOTS) pada materi klasifikasi makhluk hidup untuk peserta didik Sekolah Menengah Pertama (SMP). Rendahnya capaian keterampilan berpikir tingkat tinggi peserta didik SMP, ditandai oleh kurangnya integrasi materi HOTS dalam bahan ajar yang tersedia, menunjukkan adanya gap antara tuntutan kurikulum dan praktik pembelajaran saat ini. Pengembangan bahan ajar ini diperlukan untuk menjawab permasalahan tersebut dan memberikan kontribusi ilmiah berupa instrumen yang teruji untuk meningkatkan mutu pembelajaran IPA. Penelitian menggunakan model pengembangan 4D (Define, Design, Develop, Disseminate) yang direduksi hingga tahap Develop. Subjek uji coba meliputi ahli materi, ahli desain pembelajaran, guru IPA, dan peserta didik kelas VII. Teknik pengumpulan data dilakukan melalui validasi ahli, dengan analisis deskriptif kuantitatif dan kualitatif. Hasil validasi menunjukkan bahan ajar sangat valid dengan skor rata-rata 3,72 dari skala 4 dan nilai reliabilitas Cronbach’s Alpha sebesar 0,91, mengindikasikan konsistensi internal yang tinggi.